Local Tax Administration in Turkey - (:unkn) unknown (MALIYE BAKANLIGI, 2015)
In this article, the matter of local tax administration in Turkey is discussed in detail. Tax administration is a broad and multi-dimensional process which starts with imposing taxes and continues through the tax collection. Because of this reason, it contains many stages and actors related to each other. In the article, first of all the concept of tax administration, principles, actors and tax administration regimes are considered in a broad perspective and then local tax administration in Turkey is examined as follows: 1) Characteristics of local taxes, principles and legal framework, 2) Actors of local tax administration, 3) Phases of local tax administration. In conclusion, the problems contained within the Turkish local tax administration are discussed and suggestions for efficient local tax administration are developed within this article.
Keywords: Local Taxation; Tax Administration; Local Tax Administration